y2012 = y0 = 23,000, x = number of years since 2012

y1 = 23,000 + 23000 (0.02x) = 23,460

yn = 23,000 + y(n-1)(0.02)(x)

For year n, population is 23000 + y(n-1) * (0.02)(x)

Apr 28th, 2015

Sorry, I did it wrong. Here is the correct one:

y2012 = y0 = 23,000

y1 = 23,000 + 23,000 (0.02) = 23,460

y1 = 23,000 (1 + 0.02)

y2 = y1 (1 + 0.02)

yx = [y (x-1)] * (1+ 0.02) where x is the number of years since 2012. Don't use the yn for number of years since 2012. I made a mistake using that instead of yx so x = (current year - 2012)

I tried to multiply the number of years times 0.02 to see if that would work but it doesn't. The only thing that does work is using the previous answer to get the current year answer. The x isn't really part of the equation, it just tells you to start with the previous answer. I couldn't figure it out so the x is actually IN the equation, however I did make it so that x is the number of years since 2012, labeling 2012 as y0, then y1, y2, etc.